THE EFFECT OF MYCORRIZA TO THE INCREASE OF PLANT HEIGHT AND STEM DIAMETER OF SENGON FROM VARIOUS SEED SOURCES - Eva Vanodya Mutiarahma; Chimayatus Solichah; Tutut Wirawati; Liliana Baskorowati; Nur Hidayati; Siti Husna Norrohmah (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2020)
The purpose of this study was to determine the effect of sengon breed stock and mycorrhiza in increasing plant height and stem diameter. This research was conducted from April 2019 to September 2019 at the Center for Research and Development of Biotechnology and Forest Plant Development in Yogyakarta. Two-factor complete randomized design with 3 replications were used in this study. First factor is seed source, namely I1 = 1-1-63-1, I2 = 1-8-77-4, I3 = Malang (Bulk), and I4 = Solomon (Bulk) and second factor is the dose of mycorrhiza, namely M0 = without mycorrhiza, M 1 = mycorrhiza 5 g/plant, M2 = mycorrhiza 10 g/plant, M3 = mycorrhiza 15 g/plant. Plant height and stem diameter were collected for data. Variance analysis (ANOVA) were used at α level 5% and continued with Duncan's Multiple Range Test (DMRT) at α level 5%. The results of the study showed interactions on combinations that were in line with mycorrhiza doses on plants height and stem diameter of 8 week after planting. Parent 1- 8-77-4 gives the best results on plants height. Seed source 1-8-77-4, 1-1-63-1, and Solomon (Bulk) gives the best stem diameter results. Mycorrhizae can increase plant growth in terms of plant height and diameter.Keyword: mycorrhizae, gall rust disease, Sengon.